Maladies carcérales et salubrité publique, la crainte des contagions dans les Alpes Maritimes au XIXe siècle - Aline Martinet (Criminocorpus)
The mission of the prison is to purify society from the crimes and offenses committed by the inmates. The hygienic perception of the prison is in contradiction with the reality lives by the inmates in the cells. Prisons contain a heterogeneous crowd of unhealthy and miserable people which encourage the development of diseases and epidemics. This contribution analyzes prison diseases and the different treatments given to prisoners in the 19th century in the Alpes-Maritimes prisons.